LncRNACASC9 promotes proliferation, metastasis, and cell cycle inovarian carcinoma cells through cyclinG1/TP53/MMP7 signaling. Issue 1 (1st January 2021) - Sun, Min; Chen, Yanan; Liu, Xiaobei; Cui, Yajie
ABSTRACT: Ovarian cancer (OC) brings about serious physical and psychological burden for female patients. LncRNA CASC9 has been reported to be intimately linked with the occurrence and development of several tumors. However, the biological role of lncRNA CASC9 in OC still lacks sufficient evidence. The expressions of CASC9 and miR-488-3p in OC cell lines and xenograft mice were detected by qRT-PCR assay. Cell Counting Kit-8 (CCK-8) assay was used to assess cell inhibition rate and cell proliferation in OVCAR-3 and OVCAR-3/DDP cells. Wound healing assay and transwell assay were performed to evaluate the capacity of migration and invasion, respectively. In addition, cell apoptosis was measured by TUNEL assay and cell cycle was assessed by flow cytometric analysis. Moreover, western blotting was carried out to detect the cyclinG1 (CCNG1)/TP53/MMP7 signaling and apoptosis-related proteins. Furthermore, luciferase reporter assay was performed to verify the combination of CASC9 with CCNG1 and miR-488-3p. The results of our study revealed that CASC9 expression was upregulated while miR-488-3p and CCNG1 expression was downregulated in OC cells with significant higher TP53 and MMP7 protein levels compared with normal ovarian surface epithelial cells. Additionally, luciferase reporter assay confirmed CASC9 bond to miR-488-3p/CCNG1. CASC9 silencing inhibited cell proliferation, migration, and invasion whereas promoted cell inhibition rate and apoptosis in vitro and in vivo. However, CASC9 overexpression showed the opposite effects. In summary, LncRNA CASC9 played a regulative role in ovarian carcinoma by cyclinG1/TP53/MMP7 signaling via binding to miR-488-3p in vivo and in vitro.